2016
DOI: 10.1080/15428052.2016.1225535
|View full text |Cite
|
Sign up to set email alerts
|

Grape Pomace Skins and the Effects of Its Inclusion in the Technological Properties of Muffins

Abstract: The present study evaluated the incorporation of 5, 7.5, and 10% of Riesling skin flour (RSF) and Tannat skin flour (TSF) as wheat flour replacement in muffins. The flour was evaluated for gluten content and Alveograph parameters. The finished products were evaluated for chemical composition and technological properties, and a sensory analysis was performed. All samples presented higher dietary fiber content than wheat flour, and this was mainly in the form of soluble dietary fiber. The inclusion of grape skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
70
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 29 publications
13
70
1
2
Order By: Relevance
“…The decrease of free water in dough or the rigid nature of the fibers from GPF may cause the increase in P value of dough enriched with GPF. Similar results were reported by Bender et al () who made an addition of grape skin flour as fiber source.…”
Section: Resultssupporting
confidence: 91%
“…The decrease of free water in dough or the rigid nature of the fibers from GPF may cause the increase in P value of dough enriched with GPF. Similar results were reported by Bender et al () who made an addition of grape skin flour as fiber source.…”
Section: Resultssupporting
confidence: 91%
“…No significant differences (p > 0.05) were found between the samples for the attributes of appearance, aroma and colour. Similar results were verified by Bender et al (2016) for colour and aroma on analyzing muffins with the addition of grape skin (5%, 7.5% and 10%). Although the children found no differences for these attributes, the muffins containing JSF were darker in colour due to the large amount of anthocyanins present in the jaboticaba skin (732.77 mg.100 g -1 ) (LEITE-LEGATTI et al, 2012).…”
Section: Palavrassupporting
confidence: 70%
“…The addition of fiber-rich ingredients affects dough rheological properties (Table 5), depending on the addition level (Arufe et al, 2017;Bender et al, 2017;Elawad et al, 2016;Kurek, Wyrwisz, Karp, Brzeska, & Wierzbicka, 2017;Mironeasa et al, 2019a;Shiau, Wu, & Liu, 2015) and particle size Kurek, Wyrwisz, Piwińska, & Wierzbicka, 2016;Mironeasa et al, 2019c;Wang, Hou, & Dubat, 2017), the changes leading especially to the dilution effect of the main endogenous biopolymers such as starch and gluten, which give dough viscoelastic properties (Elawad et al, 2016;Shiau et al, 2015). The addition of high amounts of fibers in wheat dough can cause negative effects on final product volume, porosity, and crumb color darkening, but the addition of an appropriate proportion of soluble and insoluble fibers and/or enzymes such as hemicelluloses and pentosans can minimize these effects (Koletta, Irakli, Papageorgiou, & Skendi, 2014;Kurek et al, 2016).…”
Section: Dough Rheology and Wheat Flour Properties As Influenced By Gmentioning
confidence: 99%
“…Many studies revealed that winery byproducts can be used to enhance food products such as bread, muffins, cookies, biscuits, or pasta (Aksoylu, Çağindi, & Köse, 2015;Bender et al, 2017;Gaita, Alexa, Moigradean, & Poiana, 2018;Kuchtová et al, 2018;Mironeasa et al, 2019a;Smith & Yu, 2015). The addition of grape byproducts in bakery and pastry products influences dough rheology and final product texture, nutritional value, and sensory characteristics (Aghamirzaei, Peighambardoust, Azadmard-Damirchi, & Majzoobi, 2015;Boudová Pečivová et al, 2014;Gaita et al, 2018;Kuchtová et al, 2018;Maner et al, 2017;Mironeasa et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%